E-Claim System For Health Insurance And Social Security (BPJS) Types In Indonesia: Innovation And Effectiveness Of Services - Hadi Saputra, Wachyoe; Prima, Agus (Journal of Society Medicine, 2022)
There are four situations in the use of Hospital Information Technology applications or better known as SIMRS in Indonesian hospitals, first, the hospital has not had SIMRS yet, second, the hospital already has SIMRS but it has not been integrated, third, the hospital has an integrated SIMRS based on non-web service but has not bridged with E-claim application, and fourth, the hospital already has SIMRS based on Web Services and bridged with INA-CBG's E-Claim Application. The purpose of this study was to discuss the effectiveness of the National Health Insurance ( JKN ) Inpatient Claim using an integrated SIMRS web-based (Bridging System) with the INA-CBG'S E-Claim application Version 5.2 at Indonesia. Electronic Claims (E-Claims) or the INA-CBG's application is one of the patient data entry tools used to group rates based on data derived from medical resumes. The INA-CBG's E-Claim application has been installed in hospitals that serve JKN participants.